Fat: an evolving issue - John R. Speakman; Stephen O'Rahilly (The Company of Biologists, 2012)
Summary Work on obesity is evolving, and obesity is a consequence of our evolutionary history. In the space of 50 years, we have become an obese species. The reasons why can be addressed at a number of different levels. These include separating between whether the primary cause lies on the food intake or energy expenditure side of the energy balance equation, and determining how genetic and environmental effects contribute to weight variation between individuals. Opinion on whether increased food intake or decreased energy expenditure drives the obesity epidemic is still divided, but recent evidence favours the idea that food intake, rather than altered expenditure, is most important. There is more of a consensus that genetics explains most (probably around 65%) of weight variation between individuals. Recent advances in genome-wide association studies have identified many polymorphisms that are linked to obesity, yet much of the genetic variance remains unexplained. Finding the causes of this unexplained variation will be an impetus of genetic and epigenetic research on obesity over the next decade. Many environmental factors - including gut microbiota, stress and endocrine disruptors - have been linked to the risk of developing obesity. A better understanding of gene-by-environment interactions will also be key to understanding obesity in the years to come.